Candida albicans peritonitis in a patient with Felty's syndrome. Issue 4 (24th March 2005) - Thomas, D W; Munuswamy, P; Adu-Poku, K; Holgate, C S; Hickling, P; Lambert, A; Prentice, A G
Abstract : A 53 year old man with Felty's syndrome presented with abdominal pain and fever. He underwent a laparotomy after starting broad spectrum antibiotics. An intestinal biopsy showed skip ulcers with fungal hyphae. Peritoneal exudates grew Candida albicans . He was started on intravenous fluconazole and then switched to liposomal amphotericin to which he showed a good clinical response. After one month at home he was readmitted with candidosis and died of a myocardial infarction.